Gazelle tracks - Ṭaḥāwī, Mīrāl (Modern Arabic literature, 2008)
"This short but cleverly crafted novel recounts the tale of Muhra, a young woman whose name means filly, born of the descendants of the Bedouin tribes who settled in Egypt's Delta Province of El Sharqiyya during the 18th and 19th centuries." "Past mingles with present and myth and folklore blend with reality, as the narrative voice records Muhra's quest as she seeks to discover the truth about her mother through the old family photographs that adorn the walls of her grandfather's house and other documents hidden away in cupboards and drawers." "At once both narrator and narrated, Muhra's tale of self discovery is set against the dwindling fortunes of her own people as they struggle to preserve their identity and culture amid the larger Egyptian community that encroaches upon them. At the same time her father's wanderings and ultimate demise reflect the waning star of the Arab tribes who once controlled large swathes of Egyptian territory and enjoyed the patronage of Kings and Princes." "Unwilling to give up despite premonitions of doom, Muhra's search leads her inexorably to the bitter truth about her mother's poignant life and tragic and untimely end."--Jacket.